Impact of Metal Ions in Porphyrin‐Based Applied Materials for Visible‐Light Photocatalysis: Key Information from Ultrafast Electronic Spectroscopy. Issue 33 (10th July 2014) - Kar, Prasenjit; Sardar, Samim; Alarousu, Erkki; Sun, Jingya; Seddigi, Zaki S.; Ahmed, Saleh A.; Danish, Ekram Y.; Mohammed, Omar F.; Pal, Samir Kumar
Abstract Protoporphyrin IX‐zinc oxide (PP‐ZnO) nanohybrids have been synthesized for applications in photocatalytic devices. High‐resolution transmission electron microscopy (HRTEM), X‐ray diffraction (XRD), and steady‐state infrared, absorption, and emission spectroscopies have been used to analyze the structural details and optical properties of these nanohybrids. Time‐resolved fluorescence and transient absorption techniques have been applied to study the ultrafast dynamic events that are key to photocatalytic activities. The photocatalytic efficiency under visible‐light irradiation in the presence of naturally abundant iron(III) and copper(II) ions has been found to be significantly retarded in the former case, but enhanced in the latter case. More importantly, femtosecond (fs) transient absorption data have clearly demonstrated that the residence of photoexcited electrons from the sensitizer PP in the centrally located iron moiety hinders ground‐state bleach recovery of the sensitizer, affecting the overall photocatalytic rate of the nanohybrid. The presence of copper(II) ions, on the other hand, offers additional stability against photobleaching and eventually enhances the efficiency of photocatalysis. In addition, we have also explored the role of UV light in the efficiency of photocatalysis and have rationalized our observations from femtosecond‐ to picosecond‐resolved studies.